The in vitro neuroprotective activity of analogues of N-terminus substituted glyprolines - S. V. Nikolaev; I. O. Logvinov; K. N. Koliasnikova; E. A. Kuznetsova; P. I. Antipov; T. A. Antipova (LLC "Publisher OKI", 2020)
In this work investigated the neuroprotective activity of analogues of substituted glyproline GZK-111 at the N-terminus in vitro. Oxidative stress caused by H2O2 (1.5 mM) led to significant decrease in the hippocampal cells HT-22 viability. The ethyl ester N-phenypropionyl-glycyl-proline (GZK-45) was effective at the concentrations up to 10-6 M in both experimental schemes. The compounds with N-acethyl (GZK-49) and N-capronoyl (GZK-46) fragments did not protective effect in both experimental schemes. GZK-45 also had protective effect in the 6-hydroxydopamine induced damage of SH-SY5Y neuroblastoma cells.